Inside Cover: Quantum Defects as a Toolbox for the Covalent Functionalization of Carbon Nanotubes with Peptides and Proteins (Angew. Chem. Int. Ed. 40/2020). Issue 40 (4th August 2020) - Mann, Florian A.; Herrmann, Niklas; Opazo, Felipe; Kruss, Sebastian
Abstract : sp 3 quantum defects can be used for covalent functionalization of single‐walled carbon nanotubes (SWCNTs) under preservation of their near‐infrared (NIR) fluorescence. In their Research Article on page 17732, S. Kruss and co‐workers describe how peptide chains are directly grown on the SWCNT sidewall by using an Fmoc‐protected phenylalanine defect. A second maleimide defect enables attachment of proteins via thiol groups. This chemistry provides access to NIR‐fluorescent SWCNT bioconjugates and applications in photonics, biosensing, and medicine.